CRITERIA AND INDICATORS OF THE APPLYING EFFICIENCY OF ELECTRONIC OPEN JOURNAL SYSTEMS IN THE PEDAGOGICAL RESEARCHES - Luparenko , Л. А. (Journal of Information Technologies in Education (ITE), 2018)
In the article, the criteria (design, organizational and communication, productive) and indicators of efficiency of the use of electronic open journal systems (EOJS) in scientific and pedagogical research are elaborated. A sufficient level of projective criteria (67%) and high level of organizational and communication (80%) and effective (100%) criteria was established by an expert evaluation. The concept of "ICT-competence of scientific workers on the use of EOJS in scientific and pedagogical researches" was specified. The motivational-value, cognitive, operational-activity, adaptive components of ICT-competence are singled out and the criteria (axiological, cognitive, praxeological, and adaptive) and the indicators of its evaluation are specified. As a result of expert evaluation by ranking method, the most significant criterial indicators are specified, which should be guided in the process of assessing the ICT competence of scientists on the use of the EOJS in scientific and pedagogical research. The characteristic of levels of ICT-competence components’ formation (basic, sufficient, in-depth) is given. The criteria for evaluating scientific periodicals for inclusion in the leading international scientometric and abstract databases Web of Science (WoS), Scopus, Directory of Open Access Journals (DOAJ) are considered